2014
DOI: 10.1074/jbc.m113.528943
|View full text |Cite
|
Sign up to set email alerts
|

Leptin Signaling Is Required for Leucine Deprivation-enhanced Energy Expenditure

Abstract: Background: Leucine deprivation decreases fat mass via enhancing energy expenditure; the involvement of leptin signaling is unknown. Results: Leucine deprivation promoted leptin signaling, and the increased energy expenditure was blocked in leptin signalingdisrupted mice. Conclusion: Leptin signaling is required for leucine deprivation-increased energy expenditure. Significance: Our studies reveal a physiological mechanism linking leptin signaling with leucine deprivation-enhanced energy expenditure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(27 citation statements)
references
References 53 publications
1
25
1
Order By: Relevance
“…In that study, there was an increase in UCP1 mRNA and protein levels in BAT, and while UCP1 mRNA levels were not measured in WAT, there was increased lipolysis, fatty acid synthase activity, an increase in expression of β‐oxidation genes, and a decrease in lipogenic genes . These effects were due to leptin signaling as effects were abolished in db/db mice.…”
Section: Agents That Increase Browning Of White Adipose Tissuementioning
confidence: 84%
“…In that study, there was an increase in UCP1 mRNA and protein levels in BAT, and while UCP1 mRNA levels were not measured in WAT, there was increased lipolysis, fatty acid synthase activity, an increase in expression of β‐oxidation genes, and a decrease in lipogenic genes . These effects were due to leptin signaling as effects were abolished in db/db mice.…”
Section: Agents That Increase Browning Of White Adipose Tissuementioning
confidence: 84%
“…Low-fructose and high-fat diets induce leptin resistance, but animals fed high-fructose and high-sugar diets are sensitive to exogenous leptin administration, suggesting a beneficial effect of sugars in comparison to fat [55,56]. Conversely, a lack of leucine in the diet improves leptin signalling and the leptin response in animals fed with a standard diet and recovers leptin sensitivity in animals fed a sustained high-fat diet [57]. Other possible explanations for leptin resistance and obesity development may be related to epigenetic mechanisms [58].…”
Section: Molecular Mechanisms Involved In Leptin Resistancementioning
confidence: 85%
“…Chemo-resistance and radio-resistance are the principal causes of failure for pancreatic cancer patients to respond to therapy and some studies also suggest that a number of genes or mechanisms are involved in the development of pancreatic cancer [34][35][36][37]. Recombinant methionyl human leptin, an analog of human leptin has been approved by FDA for the treatment of Metabolic Abnormalities associated with Lipodystrophy [1][2][3][4][5][6][7]. We postulate that leptin, in combination with other agents, might be a potential strategy for the treatment of pancreatic cancer, especially for those with high expression of HIF-1.…”
Section: Discussionmentioning
confidence: 99%
“…In humans, there are at least four isoforms with different C-terminal cytoplastic domains. The full long form of Ob-Rl has full signaling potential, whereas the other short forms (Ob-Rs) lack major domains to mediate downstream effectors with unclear biological functions [7]. We have recently found that both Ob-Rl and Ob-Rs were expressed in pancreatic cancer tissues and cell lines, but the regulatory mechanism of Ob-R remains to be defined.…”
Section: Introductionmentioning
confidence: 98%